2019
DOI: 10.1038/s41598-019-42375-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of immune responses against the basement membrane component collagen type IV does not affect the development of atherosclerosis in ApoE-deficient mice

Abstract: Oxidation of low-density lipoprotein (LDL) in the arterial extracellular matrix results in malondialdehyde (MDA)-modifications of surrounding matrix proteins. We have recently demonstrated an association between high levels of autoantibodies against MDA-modified collagen type IV and risk for development of myocardial infarction. Collagen type IV is an important component of the endothelial basement membrane and influences smooth muscle cell function. We hypothesized that immune responses against collagen type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Analyses of induced antibodies in mice were performed mainly as previously described by Vallejo et al 32 . p210, p210-PADRE, or PADRE peptides were used for coating (20 μg/mL of each in PBS) microtiter plates (Nunc MaxiSorp, Nunc) over night at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of induced antibodies in mice were performed mainly as previously described by Vallejo et al 32 . p210, p210-PADRE, or PADRE peptides were used for coating (20 μg/mL of each in PBS) microtiter plates (Nunc MaxiSorp, Nunc) over night at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Single-cell suspensions of splenocytes were prepared by pressing spleens through a 70-μm cell strainer (BD Falcon) as previously described 32 . Erythrocytes were removed using red blood cell lysing buffer (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, in the case of collagen IV, its participation in the immunoreactivity of basement membrane in the inflammatory process was demonstrated [66,67]. In addition, it has been found that an elevated level of collagen IV, as well as the presence of collagen IV fragments, may be either a biomarker of the disease state [68][69][70] or show variable biological activity, such as cell growth, differentiation and migration, regulators of angiogenesis, inhibitors of metalloproteinases, dipeptidylpeptidase-IV [71][72][73][74].…”
Section: Research On Biological Activity Of Collagen IV Fragmentsmentioning
confidence: 99%
“…The subendothelial retention and oxidation of LDL also results in MDA-modifications of surrounding extracellular matrix proteins, including fibronectin, collagen type I-IV and ten ascin-C [ 30 , 31 ], giving rise to new potential antigens. MDA-collagen type IV-specific IgG antibodies were shown to be associated with more severe carotid disease and increased risk of myocardial infarction [ 32 ].…”
Section: Pathways Of Lipid Oxidation and Their Relevance For Atherosclerosismentioning
confidence: 99%
“…Conversely, certain lipids and their derivatives may serve as M2 macrophage polarization signals. Among such agents are 9-oxononanoyl-cholesterol, a major cholesteryl ester oxidation product [ 31 ], and resolvin D1 [ 11 ].…”
Section: Oxldl As a Macrophage Polarization Signalmentioning
confidence: 99%